HIV knowledge and its correlation with the Undetectable = Untransmittable slogan in Brazil - Rayane C. Ferreira; Thiago Silva Torres; Luana Monteiro Spindola Marins; Maria das Graças B. Ceccato; Daniel R. B. Bezerra; Paula M. Luz (Universidade de São Paulo, 2022)
ABSTRACT Knowledge about HIV transmission and prevention is a necessary step for adopting preventive behaviors. We assessed HIV knowledge and its correlation with the perceived accuracy of the "Undetectable = Untransmittable" (U=U) slogan in an online sample with 401 adult Brazilians. Overall, 28% of participants showed high HIV knowledge level. The perceived accuracy of the U=U slogan significantly correlated with HIV knowledge. Younger participants, those reporting lower income or lower education, or who had never tested for HIV showed poorer HIV knowledge. Filling gaps of knowledge among specific populations is urgent in order to increase preventive behaviors and decrease HIV stigma.